AN ETHICAL MARKETING PERSPECTIVE: CORPORATE SOCIAL RESPONSIBILITES FOR STRENGTHENING CORPORATE BRAND MANAGEMENT (STUDY CASE IN FAST MOVING CONSUMER GOODS IN INDONESIA) - Elistia, Elistia (Lembaga Penerbitan Unversitas Esa Unggul, 2016)
AbstractIn this 21st century perspective of marketing strategy for strengthening brand management are very important in business. Using principal of business ethic focusing ini ethical marketing will help stong brand in consumer mind. Ethical marketing activities are shown in Corporate Social Responsibilites affect Brand Strengthening. In recent years the surrounding world has had an increased interest, focus and demand for responsibility and sustainability. Therefore, A corporation’s formulation of its ideal identity should reflect how the firm wants to deal with the social and environmental aspects of its business. This first step is the most difficult one because a firm’s management has to adapt the definition of the desired identity to the ideal identity, whereas management is predisposed to strive for their conception of the desired identity. For instance, the desired identity may be that management wants to develop an excellent sustainable business, whereas the consumer does not reward the efforts that are made in this respect. The reflection on the ideal identity with respect to CSR should lead to a choice for one or more of the following CSR strategies: reputation management, building a virtuous corporate brand, and ethical product differentiation. As the result, the brand will win the consumer mind according to the marketing research from well-known market research companies in Indonesia. Keywords: business ethic, ethical marketing, brand management, AbstrakDalam perspektif abad ke-21 ini strategi pemasaran untuk memperkuat manajemen merek sangat penting dalam bisnis. Menggunakan prinsip etika bisnis yang berfokus pemasaran etis Penyanyi akan membantu merek stong di benak konsumen. kegiatan pemasaran etis ditampilkan di Perusahaan responsibilites Sosial mempengaruhi Merek Penguatan. Dalam beberapa tahun terakhir dunia sekitarnya telah memiliki peningkatan minat, fokus dan permintaan tanggung jawab dan keberlanjutan. Oleh karena itu, formulasi A korporasi identitas yang ideal harus mencerminkan bagaimana perusahaan ingin berurusan dengan aspek-aspek sosial dan lingkungan dari bisnisnya. Langkah pertama ini adalah yang paling sulit karena manajemen perusahaan memiliki beradaptasi definisi identitas yang diinginkan dengan identitas yang ideal, sedangkan manajemen cenderung untuk berjuang untuk konsepsi mereka dari identitas yang diinginkan. Misalnya, identitas yang diinginkan mungkin bahwa manajemen ingin mengembangkan bisnis yang berkelanjutan sangat baik, sedangkan konsumen tidak menghargai upaya yang dilakukan dalam hal ini. Refleksi tentang identitas yang ideal sehubungan dengan CSR harus mengarah pilihan untuk satu atau lebih strategi CSR berikut: manajemen reputasi, membangun merek perusahaan berbudi luhur, dan diferensiasi produk etis. Sebagai hasilnya, merek akan memenangkan pikiran konsumen menurut riset pemasaran dari perusahaan riset pasar yang terkenal di Indonesia. Kata kunci: etika bisnis, etis pemasaran, manajemen merek